Ser PositHIVo: relatos da aids em Pernambuco - Silva, Jonas Lucas Vieira da (2016)
This report describes the rationale and the creation of a book-report about those living with HIV/aids in the state of Pernambuco. The product was made to be a communication channel that exposes the needs of HIV-positive and discusses the relationship between them, the government and the society. Through it, we seek to discuss regarding the actions that must be performed for the rights of those with positive HIV status, and demystify several issues relating to HIV positive with regard to stigma and prejudice by which they pass. This research arose from the need to think about the various forms of journalism contribution to the understanding and discussion of those living with aids. The intention of create this study assumes that the understanding of the various existing realities in the works written by journalists can contribute to understand and experience the narrated facts. It is intended, thus, evident that the book-report, used by journalists to narrate the events and assist in the understanding of important facts to humanity, is a product suitable to address the issues about HIV and aids.